Answer:
[tex]y = -9x +52[/tex]
Step-by-step explanation:
Given
[tex](x_1.y_1) = (5,7)\\[/tex]
[tex](x_2,y_2) = (6,-2)[/tex]
Required
Determine the equation in slope intercept form
First, we calculate the slope of the line:
[tex]m = \frac{y_1 - y_2}{x_1 - x_2}[/tex]
This gives:
[tex]m = \frac{7 - (-2)}{5 - 6}[/tex]
[tex]m = \frac{7 +2}{-1}[/tex]
[tex]m = \frac{9}{-1}[/tex]
[tex]m = -9[/tex]
Th equation is then calculated using:
[tex]y - y_1 = m(x - x_1)[/tex]
This gives:
[tex]y - 7 = -9(x - 5)[/tex]
Open bracket
[tex]y - 7 = -9x +45[/tex]
Make y the subject
[tex]y = -9x +45+7[/tex]
[tex]y = -9x +52[/tex]